Use of lytic bacteriophage for control of experimental Escherichia coli septicemia and meningitis in chickens and calves - Barrow, Paul; Lovell, Margaret; Berchieri Jr., Angelo [UNESP] (My University, 1998)
A lytic bacteriophage, which was previously isolated from sewage and which attaches to the K1 capsular antigen, has been used to prevent septicemia and a meningitis-like infection in chickens caused by a K1+ bacteremic strain of Escherichia coli. Protection was obtained even when administration of the phage was delayed until signs of disease appeared. The phage was able to multiply in the blood. In newly borne colostrum-deprived calves given the E. coli orally, intramuscular inoculation of phage delayed appearance of the bacterium in the blood and lengthened life span. With some provisos there is considerable potential for this approach to bacterial-disease therapy.
Keywords: antiinfective agent; animal experiment; bacteriophage; cattle; chicken; controlled study; escherichia coli; intramuscular drug administration; lytic bacteriophage; meningitis; mortality; nonhuman; priority journal; septicemia; sewage; Animals; Bacteremia; Cattle; Cattle Diseases; Chickens; Coliphages; Escherichia coli; Escherichia coli Infections; Meningitis, Bacterial; Poultry Diseases; Specific Pathogen-Free Organisms